School Autonomy and Accountability in Thailand : A Systems Approach for Assessing Policy Intent and Implementation - Arcia, Gustavo; MacDonald, Kevin; Patrinos, Harry Anthony (World Bank Group, Washington, DC, 2014)
There is a consensus on the need for Thailand to reform its education system to be able to compete with other high performing countries in the region. In terms of learning outcomes, the most recent evidence from the Programme for International Student Assessment shows little improvement over time. This paper uses the World Bank's Systems Approach for Better Education Results (SABER) approach in Thailand to contrast policy intent and policy implementation in school autonomy and accountability. The policy implementation data were obtained from a survey of school principals of the schools that participated in the Programme for International Student Assessment and merged the data sets. First, the study analyzes the gap between policy intent and policy implementation. Then it examines the effect of the gaps on various schooling outcomes while controlling for covariates. The analysis finds significant differences between the Systems Approach for Better Education Results indicators of policy intent and policy implementation in all areas assessed by the indicators. Schools in Thailand exercise more flexibility in their personnel management in practice than what is intended by policy; student assessments need to address issues of content, reliability, and validity and school accountability needs to improve the interpretation of student assessments to make schools more accountable. There is a positive association between the Programme for International Student Assessment scores and school autonomy and accountability.